2017
DOI: 10.14421/jpi.2017.62.265-292
|View full text |Cite
|
Sign up to set email alerts
|

Authority of Spiritual Leadership at Pesantren Temboro Based on Jamaah Tabligh Ideology

Abstract: Kiai is a charismatic figure who has influence for the existence of pesantren. Spiritual leadership is a typology of kiai based on the values of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 1 publication
0
21
0
4
Order By: Relevance
“…47 Badruzzaman et al also says that the charismatic authority of teungku encourages total obedience as the source of Islamic values, the determiner of the way of thinking, and the act of Acehnese. 48 Tgk. Wardani; one of the caretakers in women's Dayah MUDI who has served for 11 years agreed to Tgk.…”
Section: Findings and Discussion Charismatic Authority Of Teungku Daymentioning
confidence: 99%
“…47 Badruzzaman et al also says that the charismatic authority of teungku encourages total obedience as the source of Islamic values, the determiner of the way of thinking, and the act of Acehnese. 48 Tgk. Wardani; one of the caretakers in women's Dayah MUDI who has served for 11 years agreed to Tgk.…”
Section: Findings and Discussion Charismatic Authority Of Teungku Daymentioning
confidence: 99%
“…Based on the above definition, it can be concluded that curriculum management is an activity designed to facilitate education managers in carrying out teaching and learning activities starting from the planning stage and ending with program evaluation, so that teaching and learning activities can be well directed (Arifin, 2017).…”
Section: Curriculummentioning
confidence: 99%
“…Kedua, otoritas karismatik bersumber pada kualitas spiritual kiai dan diperkuat dengan karomah. Ketiga, otoritas rasional bersumber pada usaha rasional kiai dalam membuka madrasah-madrasah formal sebagai bentuk modernisasi lembaga pendidikan Islam (Arifin, 2017).…”
Section: Sumber Otoritas Kepemimpinan Karismatik Tgh Syahri Ramadhanunclassified
“…Syahri Ramadhan nampak dari wibawa beliau yang mampu mempengaruhi masyarakat dan warga pondok pesantren, sehingga timbul ketaatan dan kepatuhan masyarakat dan warga pondok pesantren tanpa ada keraguan sedikitpun. Sumber otoritas karismatik terletak pada kualitas individu kiai, yang tidak dimiliki atau sulit dimiliki oleh masyarakat, seperti kekuatan ibadah (spiritual), kelebihan-kelebihan, karomah, dan lain-lain (Arifin, 2017).Karisma merupakan kualitas khusus yang dimiliki oleh seseorang yang berfungsi semacam magnet, pada dasarnya terdiri dari banyak sifat. Salah satu unsur yang paling penting adalah sifat kepercayaan diri (Danim, 2010).…”
Section: Sumber Otoritas Kepemimpinan Karismatik Tgh Syahri Ramadhanunclassified